English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

given x = y

x = y
x(squared) = y(squared)
x(squared) - x(squared) = y(squared) - x(squared)
x(x - x) = (y + x)(y - x)
x(y - x) / y - x = (y + x)(y - x) / y - x
x = y + x
x = x + x
1x = 2x

where did i go wrong? where is the flaw? because 1 definitely does not equal 2.

if u get it right, automatic best answer!!

2007-07-11 16:58:23 · 5 answers · asked by tochau 5 in Science & Mathematics Mathematics

5 answers

Division by zero

x(y - x) / y - x = (y + x)(y - x) / y - x

Can't divide by y-x since x=y

2007-07-11 17:01:21 · answer #1 · answered by whitesox09 7 · 3 0

Well...you cant divide by y-x cause that equals zero and that sets off a lot of problems...

2007-07-12 00:09:06 · answer #2 · answered by (Linzee18) 5 · 0 0

the flaw is:

zero division at y - x

2007-07-12 00:02:14 · answer #3 · answered by iyiogrenci 6 · 2 0

division by zero

2007-07-12 00:11:37 · answer #4 · answered by A Military Veteran 5 · 0 0

ALSO X CANT HAVE A DIFFERENT VALUE.

2007-07-12 00:06:42 · answer #5 · answered by Anonymous · 0 2

fedest.com, questions and answers